GAYA KOMUNIKASI KEPEMIMPINAN PEREMPUAN DI KOTA TANGERANG SELATAN : Analisis Airin Rachmi Mantan Walikota Tangerang Selatan - Novianty Aulia Anjani (2022)
This study aims to find out and analyze the communication style applied by Airin Rachmi during her leadership as mayor of South Tangerang from 2010- 2021 by using the concept of communication style according to Tubss and Moss which is equipped with standpoint theory. The approach used is qualitative with etnography method. Informants in the study were selected using a purposive sampling technique based on predetermined criteria. The final result of the research shows that Airin Rachmi applies 3 types of communication namely styles equalitarian style, structuring style and relinquinshing style. Equalitarian style Airin Rachmi ustainable with relinquinshing style where Airin Rachmi emphasizes equality and openness so that employees have equal opportunity to present ideas. Airin Rachmi's habit of communicating also refers to the characteristic of women, namely private speaking who is passionate about social relations with more personal topics of conversation supported by skills as a good listener. In line with the structuring style, Airin Rachmi also avoids creating conflicts by always giving her full attention and care as a leader.